Suppression of the interleukin-1 beta-induced inflammatory response of human Chang liver cells by acute and subacute exposure to alcohol: an in vitro study - Moers, Katharina; Kany, Shinwan; Hoerauf, Jason-Alexander; Wagner, Nils; Neunaber, Claudia; Marzi, Ingo; Relja, Borna; Perl, Mario (Croatian Medical Journal, 2018)
Aim To evaluate protective immunosuppressive dose and time-dependent effects of ethanol in an in vitro model of acute inflammation in human Chang liver cells.Method The study was performed in 2016 and 2017 in the research laboratory of the Department of Trauma, Hand and Reconstructive Surgery, the University Hospital of the Goethe-University Frankfurt. Chang liver cells were stimulated with either interleukin (IL)-1 beta or IL-6 and subsequently treated with low-dose ethanol (85 mmol/L) or high-dose ethanol (170 mmol/L) for one hour (acute exposure) or 72 hours (subacute exposure). IL-6 and IL-1 beta release were determined by enzyme-linked immunosorbent assay. Neutrophil adhesion to Chang liver monolayers, production of reactive oxygen species, and apoptosis or necrosis were analyzed.Results Contrary to high-dose ethanol, acute low-dose ethanol exposure significantly reduced IL-1 beta-induced IL-6 and IL-6-induced IL-1 beta release (P < 0.05). Subacute ethanol exposure did not change proinflammatory cytokine release. Acute low-dose ethanol exposure significantly decreased inflammation-induced formation of reactive oxygen species (P < 0.05) and significantly improved cell survival (P < 0.05). Neither acute nor subacute high-dose ethanol exposure significantly changed inflammation-induced changes in reactive oxygen species or survival. Acute and subacute ethanol exposure, independently of the dose, significantly decreased neutrophil adhesion to inflamed Chang liver cells (P < 0.05).Conclusion Acute treatment of inflamed Chang liver cells with ethanol showed its immunosuppressive potential. However, the observed effects were limited to low-dose setting, indicating the relevance of ethanol dose in the modulation of inflammatory cell response.